South Caucasus - Armenia, Azerbaijan, and Georgia : Private Enterprises in the Forest Sector - A Survey of the Private Sector in Wood Production and Processing - World Bank (World Bank, Washington, DC, 2020)
In all three countries of the South Caucasus region - Armenia, Azerbaijan, and Georgia forests are a key natural resource and source of wealth for the nation and the global community. Different resource endowments have created variation in wood utilization patterns across the countries. While fuelwood production remains by far the most common type of forest use in all three countries, production forestry and wood processing differ. This study aimed to generate regional knowledge on the private sector’s role in the forest sector and to enhance opportunities for public-private collaboration to improve forest-based job creation and economic development. In the medium to long-term, this knowledge is expected to inform the countries, the World Bank, and other development partners when they develop interventions and policies that help to exploit forest resources sustainably for national development. The report focuses on wood production, harvesting, and processing but not on other forest-based direct and indirect economic activities such as tourism.